Trends and recent changes in the Latin American food and agriculture situation - Luis López Cordovez (CEPAL Review, 1982)
This paper analyses the chief trends and recent changes in the agriculture and food situation of the Latin American countries and seeks to give a brief overall picture, despite limitations arising from the insufficient and sometimes partial data.